Alterations of visual reaction time and short term memory in military radar personnel. - Seyed Mohammad Javad Mortazavi; Shahram Taeb; Naser Dehghan (Tehran University of Medical Sciences, 2013)
Radar transmitters emit high-power radiofrequency radiation by creation of a high-voltage and high-frequency alternating electrical current.Health effects of occupational exposure to military radar were investigated. Visual reaction time was recorded with a simple blind computer-assisted-visual reaction time test. To assess the short-term memory, modified Wechsler Memory Scale test was performed.The mean +/- SD reaction time in radar works (N=100) and the control group (N=57) were 238.58 +/- 23.47 milliseconds and 291.86 +/- 28.26 milliseconds (P